Black Bengal goat rearing for women entrepreneurs in West Bengal under Agri- clinics and Agri-business Scheme - Mandal, Soumyesh; Das, S N (Indian Farming, 2016)
The Government launched the Agri-Clinics and Agri-Buisness Centres as scheme to promote farm entrepreneurship among agricultural graduates, other graduates and intermediates. These Centers have been very helpful, particularly in the case of making projects where they guide the entrepreneurs to fill the basic technical and financial details in their proposals.